Relation between examinees' true knowledge and examination scores: systematic review and exemplary calculations on Multiple-True-False items. (November 2021) - Schmidt, Dennis; Raupach, Tobias; Wiegand, Annette; Herrmann, Manfred; Kanzow, Philipp
Abstract: Multiple-True-False questions are one specific type of multiple-choice item that can be used to assess knowledge in written examinations. Within Multiple-True-False items, a number of statements within a single item are given, and each statement has to be marked separately as true or false. Various scoring methods for Multiple-True-False items exist and there is no consensus as to the ideal scoring method. The study aimed to systematically identify available scoring methods for Multiple-True-False items and to assess their usability and statistical parameters (i.e. available information included and expected chance scores from random guessing). Another objective was to examine the relation between examinees' true knowledge and expected scoring results. Data presented in this manuscript may help educators make informed choices about the scoring method to be selected and corresponding pass marks required for testing a certain level of true knowledge of examinees. Highlights: Multiple-True-False items are one specific type of multiple-select items. Scoring of Multiple-True-False items is complex. 27 scoring methods have been identified from the literature. Statistical parameters were calculated for each scoring method. Relation between examinees' true knowledge and expected scoring results was assessed.